Development of interactive multimedia based on an articulate storyline to improve the independent dimension and learning outcomes of Pancasila education - Putri Rifkiyani; Kurotul Aeni (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The use of lecture methods or textbooks often causes boredom and harms students' academic achievement in Pancasila Education. To overcome this, researchers developed interactive multimedia learning media through the Articulate Storyline platform. This research aims to design, evaluate the feasibility, and determine the effectiveness of interactive multimedia learning media, utilising Articulate Storyline, to enhance the independence dimension and learning outcomes in Pancasila Education among fifth-grade students. This developmental research utilises the Borg and Gall model, which consists of eight systematic steps: needs and issue analysis, information gathering, product planning, design evaluation, design improvement, initial testing, product refinement, and implementation trial. The research participants are fifth-grade students at SDN Ngaliyan 05 Semarang. The media expert validation score was 91.67%, and the material expert's score was 98.21%, which was deemed very feasible. There was a significant increase in the independent dimension and learning outcomes of fifth-grade students of SDN Ngaliyan 05 Semarang. The N-Gain calculation showed an average increase in learning outcomes of 0,73. This research concludes that Articulate Storyline-based interactive multimedia is a successful, feasible, and practical approach for teaching Pancasila education to fifth-grade students. This research contributes to the provision of digital media innovation in Pancasila education.